Evaluation of pharmacokinetic parameters of the non-hypercalcemic calcitrol analogues EM1 and UVB1 - Guevara, Josefina Alejandra (2020)
Vitamin D analogues EM1 and UVB1 have demonstrated antitumor effects in preclinical studies employing cell lines, animal models and patient-derived xenograft cells. In the current work we focused on the study of Absorption, Distribution, Metabolism, and Excretion (ADME) properties of these analogues by SwissADME software, an in silico tool. The results showed that the analogues have simi- lar lipophilicity to calcitriol. The resulting log Po/w values were 5.02, 6.27 and 5.03 for EM1, UVB1 and calcitriol, respectively. In addition, the polar surface area (PSA) values obtained to EM1 (85.80 Å2), UVB1 (80.92 Å2) and calcitriol (60.69 Å2) suggest the ability of the analogues to cross cell membranes such as the blood-brain barri- er. In accordance with these results, BOILED-egg plots predict that both analogues have high brain penetration, however they could be efflux by p-glycoprotein as the analogues are substrates of this pump. Regarding transdermal absorption, skin permeability coeffi- cients (log Kp) for EM1, UVB1 and calcitriol were -5.99 cm/s, -4.95 cm/s, -5.24 cm/s, respectively, suggesting the potential to adminis- ter these compounds by this route. Moreover, Bioavailability Radar plots indicate that EM1 has similar properties to calcitriol for oral bioavailability while UVB1 needs to decrease its flexibility, lipophilia and size to be orally administered. Finally, the in silico prediction of genotoxicity indicates that the analogues have non-mutagenic and non-carcinogenic properties in AMES tests, the probabilities were 0.8069 for EM1 and 0.94 for UVB1. Altogether, these in silico analy ses complement the reported in vitro and in vivo studies to reinforce the use of these analogues as chemotherapeutic agents.